Implementasi Program Desa Wisata Dalam Rangka Pemberdayaan Masyarakat di Desa Mas, Kecamatan Ubud Kabupaten Gianyar, Provinsi Bali - Ferry Aryanto Padabain; Saptono Nugroho (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2017)
The purpose of this research is to know the working Program of the tourist village and the extent of implementation, in the Mas village. This research was conducted in the Mas village with method survey. Data collection is done by conducting in-depth interviews and observations to the speaker. Method of sampling is random with interviewees interviewed related parties among others, Kasie extension and human resources development in the Tourism Office of Gianyar Regency, the head of the Mas village, Chairman of the Group aware of tours (Pokdarwis), and the perpetrators of the tourism. The data collected showed that the work programme of the group is aware that includes 4 programs: resources, environmental conservation, art preservation, custom and culture, Marketing and Promotionwhile the implementation of the work programme of the Group aware of the tour has been running pretty good one is the development of a Tarukan tourist village by empowering local communities so as to give a positive impact for the people's welfare. However in its development of consistency management of tourist village that is a conscious Group tours (Pokdarwis) begin to experience barriers due to resources, communications, Disposition/Implementers and workflow in the internal Group Aware that must be addressed in order for programs that have already been created can be done on an ongoing basis. Key Words: Work Programme, Implementation, Empowerment